国产伊马替尼治疗慢性髓性白血病的血药浓度与疗效分析 (Zhonghua Xue Ye Xue Za Zhi, 2019)
OBJECTIVE: To analyze the correlation between plasma trough level of generic imatinib and its metabolism and clinical outcomes in Chinese patients with chronic myeloid leukemia in chronic phase (CML-CP) . METHODS: The 21 patients with CML-CP who enrolled in a clinical trial YMTN 1.0 from Oct 11(th), 2012 to May 8(th), 2013 and received generic imatinib were as study subjects. The correlation between steady plasma trough levels of imatinib and its metabolism with clinical response, age, weight and body surface area (BSA) were evaluated. RESULTS: ①The mean steady plasma trough level of generic imatinib and its metabolism was (1 185.07±417.91) µg/L and (251.53±76.50) µg/L, respectively. ②Age, weight and BSA has no significant effects on plasma trough level of generic imatinib and its metabolism (P>0.05) . ③Patients with steady plasma trough level of generic imatinib more than 1 000 µg/L are possible to have higher major molecular response (MMR) /complete molecular response (CMR) rate than those below 1 000 µg/L (42% vs 0, P<0.05) . CONCLUSION: Plasma trough levels of generic imatinib varied in CML patients. The steady plasma trough levels of generic imatinib is maybe related to molecular response in CML patients.